Age and risk of recurrence in oral tongue squamous cell carcinoma: Systematic review. Issue 12 (11th September 2020) - Lenze, Nicholas R.; Farquhar, Douglas R.; Dorismond, Christina; Sheth, Siddharth; Zevallos, Jose P.; Blumberg, Jeffrey; Lumley, Catherine; Patel, Samip; Hackman, Trevor; Weissler, Mark C.; Yarbrough, Wendell G.; Olshan, Andrew F.; et al.
Abstract: The incidence of oral tongue squamous cell carcinoma has been increasing in young patients (≤45 years) without a clear etiologic driver. It is unknown if younger patients have an increased risk of recurrence compared to older patients. A literature search was conducted through January 2020 using PubMed/MEDLINE, Embase, Cochrane, Scopus, Science Direct, and clinicaltrials.gov . This review was registered with PROSPERO (ID: CRD42020167498) and the PRISMA statement was followed. Studies were eligible for inclusion if they assessed risk of recurrence by age using a time‐to‐event analysis, used an age cutoff of ≤45 years or less for the younger cohort, and limited the analysis to the oral tongue subsite. Data were extracted independently by two reviewers using a form with a prespecified list of variables. There were 13 articles that met criteria for the qualitative synthesis (n = 1763 patients). The reported 5‐year rates of disease‐free survival ranged from 30% to 72% for the younger cohorts and 42% to 81% for the older cohorts. Three studies reported a statistically significant increased risk of recurrence in younger patients, three studies reported a nonsignificant increased risk in younger patients, and seven studies reported a similar risk in younger patients based on the time‐to‐event analyses. There may be an increased risk of recurrence for younger patients with oral tongue cancer. A definitive conclusion is precluded by limitations among individual studies, and additional research is warranted to examine this question.